A method for filtering smoke in images - Oliveira, Marcos; Silva, Francisco; Saraiva, Arata; Ferreira, Nuno; Sousa, José (Anais da Escola Regional de Informática do Piauí (ERI-PI), 2018)
The treatment of images captured in situations where there the we have bad visibility like smoke or foggy weather conditions is a great challenge. In this sense, we have developed a technique of filtering smoke and foggy in images that have the potential to benefit many applications of understanding and computational vision. Our algorithm is based on a series of mathematical methods to capture the noise by means of its density, in the end our results demonstrate that the method is quite effective to solve the problem of the test images.